Análisis de la rentabilidad en las entidades del sector financiero de la economía popular y solidaria segmento tres en la provincia de Tungurahua cantón Ambato periodo 2021 - Quishpe Cando, Bélgica Salomé (2023)
In this research project, the profitability of 15 Cooperatives in segment 3, Province of Tungurahua, Cantón Ambato, was analyzed, a quantitative approach was used to explain the different variations of their financial profitability, additionally, sources of secondary information were used. , such as the financial bulletins obtained from the database of the web portal of the Superintendence of Popular and Solidarity Economy (SEPS) corresponding to the year 2021.